Salivary sialic acid and cancer. - (:unkn) unknown (My University, 1996)
In this preliminary study the salivary sialic acid levels in 56 randomly selected cancer patients of different ages were compared with those of 70 healthy controls of similar age distribution. The cancer patients consisted of 25 women and 31 men. Twenty were suffering from lung cancer. Unstimulated whole saliva was collected by expectoration. The mean sialic acid levels were 185 +/- 22.8 mg/dl in the cancer group and 6.2 +/- 3.72 mg/dl in the controls and the difference between them was significant (p < 0.0001). The subjects were also grouped according to age and cancer type. However there were no significant differences in sialic acid levels between these.